2013
DOI: 10.1111/ejn.12237
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies to cannabinoid type 1 receptor co‐react with stomatin‐like protein 2 in mouse brain mitochondria

Abstract: Anti-cannabinoid type 1 receptor (CB1) polyclonal antibodies are widely used to detect the presence of CB1 in a variety of brain cells and their organelles, including neuronal mitochondria. Surprisingly, we found that anti-CB1 sera, in parallel with CB1, also recognize the mitochondrial protein stomatin-like protein 2. In addition, we show that the previously reported effect of synthetic cannabinoid WIN 55,212-2 on mitochondrial complex III respiration is not detectable in purified mitochondrial preparations. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
57
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 21 publications
6
57
0
Order By: Relevance
“…The ability of cannabinoids to control mitochondrial activity was first reported in the 1970s 143 and is now thought to be a potentially important way in which eCBs influence cellular and brain functions 144,145 . Recently, the presence of functional CB1R at mitochondrial membranes was demonstrated by different groups 146,147 (see REFS 148,149 for methodological discussions). The brain mitochondrial CB1R (mtCB1R) directly regulates respiration and ATP production and, at the synaptic level, participates in eCB-dependent synaptic plasticity.…”
Section: Future Directionsmentioning
confidence: 99%
“…The ability of cannabinoids to control mitochondrial activity was first reported in the 1970s 143 and is now thought to be a potentially important way in which eCBs influence cellular and brain functions 144,145 . Recently, the presence of functional CB1R at mitochondrial membranes was demonstrated by different groups 146,147 (see REFS 148,149 for methodological discussions). The brain mitochondrial CB1R (mtCB1R) directly regulates respiration and ATP production and, at the synaptic level, participates in eCB-dependent synaptic plasticity.…”
Section: Future Directionsmentioning
confidence: 99%
“…Furthermore, CB1 receptors have been found recently on the external membrane of brain mitochondria 111 . Although this finding is still somewhat controversial 112 , these mitochondrial receptors seem to regulate neuronal energy metabolism directly, because incubation of isolated mitochondria with THC reduces the activity of the respiratory chain complex I, decreases the level of mitochondrial cAMP, and decreases mitochondrial PKA activity 112 (FIG. 1).…”
Section: Ecb Signalling Cell Metabolism and Diseasementioning
confidence: 99%
“…However, these findings were questioned by a more recent study [47], which has demonstrated that the previously used anti-CB 1 antibodies can bind to the mitochondrial protein stomatin-like protein 2, and the previously reported effects of cannabinoid agonist on mitochondrial respiration can be replicated in synaptosome-enriched, but not pure mitochondrial preparations. (4) FLAT was reported as a critical molecular component of anandamide transport in neural cells [44].…”
Section: Other Possible Mechanismsmentioning
confidence: 99%